Conditional cash transfers and their impact on child work and schooling: evidence from the PROGRESA program in Mexico - Skoufias, Emmanuel; Parker, Susan W. (International Food Policy Research Institute, 2001)
In this paper we investigate whether a conditional cash transfer program such as the Programa Nacional de Educación, Salud y Alimentación (PROGRESA) can simultaneously combat the problems of low school attendance and child work. PROGRESA is a new program of the Mexican government aimed at alleviating extreme poverty in rural areas. It combats the different causes of poverty by providing cash benefits that are targeted directly to households on the condition of children attending school and visiting health clinics on a regular basis. Some of the questions addressed are as follows: Does the program reduce child labor? Does it increase participation in school activities? Does the latter occur at the expense of children's leisure time? And how do the effects of the program vary by age group and gender? Our empirical analysis relies on data from a quasi-experimental design used to evaluate the impact of the program involving a sample of communities that receive PROGRESA benefits (treatment) and comparable communities that receive benefits at a later time (control). We estimate the effect of “treatment on the treated” using both double-difference and cross sectional difference estimators. Our estimates show significant increases in the school attendance of boys and girls that are accompanied by significant reductions in the participation of boys and girls in work activities. We also find that the program has a lower impact on the incidence of work for girls relative to boys.